Asymmetric Warfare: Challenging The Boundaries of Humanitarian Law In The Era of Contemporary Conflict - Budiman Budiman; Bambang Prasetyo Utomo; Tarsisius Susilo; Arifin Simanjuntak; Gusti Bagus Oka Tapayasa (Journal of Social Research, 2025)
Asymmetric warfare represents a transformative shift in modern conflict, characterized by the involvement of unequal forces and the increasing role of non-state actors, unconventional tactics, and emerging technologies. This study examines how asymmetric warfare challenges the implementation of international humanitarian law (IHL), particularly concerning combatant identification, proportionality in attacks, and civilian protection in fluid conflict environments. Employing a qualitative method through normative legal analysis and literature review, the research critically evaluates IHL instruments such as the Geneva Conventions and Additional Protocols in light of contemporary conflict dynamics. Case studies from Afghanistan, Syria, and Palestine are analyzed alongside developments in cyber and information warfare. The findings reveal significant limitations in existing legal definitions and enforcement mechanisms, especially with the rise of hybrid tactics and digital battlegrounds. The study proposes a framework for adapting IHL through the redefinition of combatant status, the establishment of clearer proportionality standards, and the creation of new legal instruments to regulate cyber operations and disinformation. Moreover, it emphasizes the need to enhance accountability through technology-enabled monitoring systems and to expand humanitarian law education to include non-state actors. This research contributes to the evolving discourse on modern warfare by advocating for an adaptive legal architecture that upholds human dignity amid increasingly complex conflict scenarios.